Fever Associated with Gastrointestinal Shigellosis Unmasks Probable Brugada Syndrome - John N. Makaryus; Jennifer Verbsky; Scott Schwarz; David Slotwiner (Case Reports in Medicine)
Since it was first described approximately 15 years ago, the Brugada Syndrome has spurred a significant quantity of interest in its underlying mechanism and physiology. The Brugada electrocardiographic pattern is characterized by right bundle branch block morphology and ST segment elevations in the right precordial leads with an absence of identifiable underlying structural heart disease. The syndrome is clinically significant since these patients are at a higher risk of developing malignant ventricular arrhythmias. One of the mechanisms behind the disorder involves mutations in specific myocardial sodium channels. Furthermore, these electrocardiographic changes appear to be temperature dependent. We present the case of a 35-year-old male who presented with intestinal Shigellosis and was also found to have Brugada-type electrocardiographic changes on ECG. The electrocardiographic changes that were present when the patient was admitted and febrile resolved following antibiotic therapy and defervescence.